Supplementary effect of whey components on the monascin productivity of Monascus sp. (15th February 2023) - Huang, Qingyun; Miyaki, Nodoka; Li, Zongfei; Takahashi, Yutaroh; Ishizuka, Satoshi; Hayakawa, Toru; Wakamatsu, Jun‐ichi; Kumura, Haruto
Abstract: BACKGROUND: Monascus sp. has been used in fermented foods for centuries. It can synthesize yellow, red, and orange pigments as secondary metabolites. Here, we focused on yellow pigment monascin, responsible for anti‐inflammation and antidiabetic effects, and investigated whether whey could be a suitable substrate with or without rice powder for monascin production using M . purpureus AHU 9085, M . pilosus NBRC 4520 and M. ruber NBRC 32318. RESULTS: The growth and monascin production of the three Monascus strains were dependent on three liquid media consisting of whey and/or rice. All strains showed the best growth in a rice and whey mixed medium, in which M. ruber NBRC 32318 exhibited the highest total monascin production. Subsequent investigation of the effects of whey components indicated that a mineral cocktail in whey was particularly effective in stimulating the monascin production efficiency of M. ruber NBRC 32318. However, this recipe exhibited less stimulation, or even inhibition, for M . pilosus NBRC 4520 and M . purpureus AHU 9085, respectively. In terms of total monascin production, rice with whey provided the highest amount due to growth promotion along with relatively high production efficiency. CONCLUSION: The effect of whey on growth and monascin production was strongly dependent on the Monascus strains. Even a mineral cocktail in whey could regulate monascin productivity in a strain‐specific manner. Further studies are needed to elucidate the mechanism behind the diverse responses by the minerals in the production of monascin from Monascus . © 2023 Society of Chemical Industry.